Fundamental Parameters of a Binary System Consisting of a Red Dwarf and a Compact Star - Xu Ding; KaiFan Ji; ZhiMing Song; NianPing Liu; JianPing Xiong; Qiyuan Cheng; ChuanJun Wang; JinLiang Wang; DeQing Wang; ShouSheng He (The Astronomical Journal, 2024)
TIC 157365951 has been classified as a δ Scuti type by the International Variable Star Index. Through the spectra from Large Sky Area Multi-Object Fiber Spectroscopic Telescope and its light curve, we further discovered that it is a binary system. This binary system comprises a red-dwarf star and a compact star. Through the spectral energy distribution fitting, we determined the mass of the red dwarf star as M _1 = 0.31 ± 0.01 M _⊙ and its radius as R _1 = 0.414 ± 0.004 R _⊙ . By fitting the double-peaked H α emission, we derived the mass ratio of q = 1.76 ± 0.04, indicating a compact star mass of M _2 = 0.54 ± 0.01 M _⊙ . Using Phoebe to model the light curve and radial velocity curve for the detached binary system, we obtained a red dwarf star mass of M _1 = 0.29 ± 0.02 M _⊙ , a radius of R _1 = 0.39 ± 0.04 R _⊙ , and a Roche–lobe filling factor of f = 0.995 ± 0.129, which is close to the f = 1 expected for a semidetached system. The Phoebe model gives a compact star mass M _2 = 0.53 ± 0.05 M _⊙ . Constraining the system to be semidetached gives M _1 = 0.34 ± 0.02 M _⊙ , R _1 = 0.41 ± 0.01 R _⊙ , and M _2 = 0.62 ± 0.03 M _⊙ . The consistency of the models is encouraging. The value of the Roche–lobe filling factor suggests that there might be ongoing mass transfer. The compact star mass is as massive as a typical white dwarf.